New insight in pediatric dentistry: preventive dentistry in allergy management protocol - Seno Pradopo; Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2007)
; "> The relationship between oral health and systemic diseases had been abundantly studied, however, mostly were related to adultsuch as cerebrovascular disease, cardiovascular disease, diabetes mellitus etc. Nevertheless, it was still uncommon that oral healthalso related to allergic disease. The field of pediatric dentistry is mostly related to preventive dentistry (i.e. prophylactic procedures,preventive orthodontic etc., but rarely related to preventive medicine such allergy prevention in children. Allergic diseases develop outof a close interaction between genetic predisposition and environmental triggers, and progress continuously since infancy regarding tothe allergic march. Concerning to the partially developed immunity in children, children are more susceptible to infection and allergicdiseases than adults. Unfortunately, infection and allergic diseases are interrelated; infection impaired allergy and vice versa. Poororal health is closely related to infection; however, improving oral health is not included in allergy management protocol. In order toanticipate the future, dentist or especially pediatric dentist should be able to review about basic children immunity and oral mucosalimmunity. Additionally, it is essential to explain to the parents and medical practitioners who are not familiar to this new paradigm.The objective of this study is to review articles related to children’s oral health and allergic symptoms. Regarding to the successfuloral management of allergic symptoms, the propensity that improving oral health could be included in children’s allergy managementprotocol is likely.